Pengendali Air Wudhu Otomatis Menggunakan Sensor Ultrasonik Berbasis Arduino - Primatama Kurniandisyah; M Safii; Bahrudi Efendi Damanik; Dedy Hartama; M. Ridwan Lubis (STMIK Budi Darma, 2021)
Before performing prayers, Muslims must first take ablution water. So far, the provision of ablution water from mosques and prayer rooms is almost 100% using a faucet that is turned manually, sometimes it is troublesome and water is often wasted (wasteful). Therefore, the purpose of this research is to build a prototype automatic ablution water controller in the form of developing a system with an Arduino-based ultrasonic sensor. The tool that is built based on the prototype will be able to issue ablution water automatically and stop automatically, depending on the limb that is brought close to the end of the pipe that will discharge the water. This monitoring works by using an ultrasonic sensor, where the object under the sensor becomes the input. The ultrasonic sensor will be connected to the Arduino microcontroller which is useful for running this system, which provides information on the relay to activate the mini water pump and release water. So it can be concluded that this system is able to help control the use of ablution water to be more efficient.